Hormone therapy for first-line management of menopausal symptoms: Practical recommendations. (August 2019) - Palacios, Santiago; Stevenson, John C; Schaudig, Katrin; Lukasiewicz, Monika; Graziottin, Alessandra
Hormone therapy use has undergone dramatic changes over the past 20 years. Widespread use of hormone therapy in the 1980s and 1990s came to an abrupt halt in the early 2000s after initial findings of the Women's Health Initiative trial were published and the study was terminated. Since then, much has been learned about the characteristics of women most likely to benefit from hormone therapy. There is general agreement that women younger than 60 years or who initiate hormone therapy within 10 years of menopause onset gain short-term benefit in terms of symptomatic relief and long-term benefit in terms of protection from chronic diseases that affect postmenopausal women. Despite accumulating evidence in support of hormone therapy for symptomatic menopausal women, the slow response by the medical community has led to a 'large and unnecessary burden of suffering' by women worldwide. Greater efforts are clearly needed to educate physicians and medical students about the pathophysiology of menopause and the role of hormone therapy in supporting women through the transition. This article provides a brief historical perspective of events that led to the backlash against hormone therapy, explores the current position of guideline groups, and provides practical recommendations to guide first-line management of symptomatic menopausal women.